Para-Anastomotic Pseudoaneurysms as a Long-Term Complication After Surgical Treatment of Peripheral Artery Disease: Clinical Characteristics and Surgical Treatment - Julia Łacna; Michał Serafin; Dorota Łyko-Morawska; Julia Szostek; Dariusz Stańczyk; Iga Kania; Magdalena Mąka; Waclaw Kuczmik (Biomedicines)
Background: Peripheral arterial disease (PAD) is becoming an increasingly prevalent clinical issue, leading to a growing number of patients requiring surgical interventions. Consequently, there is an increasing occurrence of para-anastomotic aneurysms as late complications following primary treatment for PAD. These aneurysms typically arise at the sites of graft implantation and necessitate individualized management strategies based on factors such as location, size, and the patient’s overall condition. Materials and Methods: This five-year retrospective study, conducted at a single center, aimed to evaluate the anatomical location, clinical presentation, diagnostic methods, and management strategies for 55 patients treated for femoral and popliteal artery para-anastomotic pseudoaneurysms of the lower limb between January 2018 and June 2024. Treatment approaches were determined based on aneurysm size, the extent of atherosclerosis, and the patient’s surgical risk. This study analyzed patient demographics, surgical techniques, postoperative complications, and aneurysm characteristics. Results: Most pseudoaneurysms occurred between 6 and 10 years after the primary procedure. The most common surgical intervention was aneurysmectomy with graft interposition, performed in 46 patients (83.64%), followed by aneurysmectomy with extra-anatomical bypass in 6 patients (10.91%), and endovascular repair (EVAR) in 3 patients (5.45%). Early postoperative complications occurred in 16.36% of patients. The 12-month freedom from graft stenosis was 87.23%, and freedom from anastomotic aneurysm recurrence at 12 months was 100%. Conclusions: This study highlights the critical need for individualized treatment strategies and ongoing surveillance in managing lower-limb para-anastomotic pseudoaneurysms, particularly given the prevalence of lower-limb pain and the high occurrence of such in the common femoral artery. The favorable long-term graft patency rates observed suggest that aneurysmectomy with graft interposition is an effective intervention, reinforcing its role as the primary approach within this patient population.